The Impact of Economy-Wide Sentiment on Analysts' Research Activities. (July 2019) - Tang, Michael; Yao, Li
In this article, we examine how economy-wide sentiment, measured with the University of Michigan's Consumer Sentiment Index, affects analysts' research activities. Using a firm-fixed effects design, we find that consumer sentiment, especially the component related to economic fundamentals, is negatively associated with analysts' frequency of issuing research reports, but is positively associated with the precision of analysts' idiosyncratic information, our proxy for analysts' engagement in private information discovery. The evidence is more pronounced for firms with larger total assets, higher return on assets, better market performance, lower stock return volatility, and higher institutional ownership. We further document that analyst reports are more informative when consumer sentiment is higher. Taken together, our findings suggest that analysts respond to higher consumer sentiment by allocating more effort to private information discovery, which enhances the informativeness of their reports to investors. Our research reveals the impact of sentiment, a macrolevel factor, on analysts' research activities, and it enriches the knowledge of analysts' decision processes.